CO Safety in Azerbaijani Residential Buildings: Legislative Framework, Costs, and Community Practices - Mammadzada, Azada; Alakbarova, Guljan; Shahmammadli, Javid (My University, 2026)
This capstone project investigates the safety of CO in residential buildings in Azerbaijan. Despite the existing laws for the safe use of gas in Azerbaijan, such as the use of detectors, technical maintenance of gas appliances, the use of specialized contractors for gas appliances, and official warnings regarding gas appliances, CO poisoning remains a health and safety risk for individuals in Azerbaijan. Statistics provided by TABIB, web-scraping carried out within this research and other reliable sources helped us identify the main policy problem of this research: there is low CO safety in Azerbaijani residential buildings. After careful examination of the official statistics, legal documents, web-scraped information from many websites, and interview results, we have identified three major factors contributing to the low CO safety in Azerbaijani residential buildings: weak implementation of existing legal framework, low affordability of safety measures, and the gap between public awareness and preventive practices. Three policy options were proposed considering the essence of the problem: improving the existing implementation framework via risk-based inspection and the visibility of technical service contractors, mandatory and supported detector policy, and raising awareness through practical seasonal risk communication and safety education. Based on the criteria of effectiveness, efficiency, equity, political acceptability and feasibility mproving the existing implementation framework through risk-based inspection and stronger contractor visibility is selected as the most suitable hort-term policy option. The other two policies were selected as supplementary ones.
Keywords: CO; residential safety; gas safety; risk communication; detector policy; public safety